ANALISIS KETIMPANGAN WILAYAH DAN ARAHAN PENGEMBANGAN WILAYAH DI KABUPATEN BURU PROVINSI MALUKU - Rifyan Ruman; Setia Hadi; Baba Barus (TATALOKA, 2018)
The purpose of this study was to determine the class-leading commodity and land capability and potential of land that can be used for agricultural development in Buru. Data analysis method used was overlying maps, Location Quotient (LQ) and Shift Share Analysis (SSA) to determine the main commodity. The result is elaborated as follow inequality in Buru can be seen from inadequate infrastructure especially the condition of road, education and health facilities. Based on analysis of LQ and SSA in the Buru Regency, Commodities priorities in this region are sweet potatoes, peanuts, green beans, peppers, onion, tomato, spinach, kale, squash, eggplant, beans, avocado, mango, jackfruit, durian, orange, papaya, banana, cashew, and clove. The potential cultivate land for each sub-districts as Namlea (22390.73 ha), District Waeapo (68615.62 ha), District of Waplau (22173.26 ha), District Batabual (7920.27 ha) and District Air Buaya (10985.77 ha) that can be utilized for the development of agriculture-based according to the vision of Buru and in accordance with the commodity that exist in each district.